EFFICIENCY SHOOTING PROGRAM FOR YOUTH BASKETBALL PLAYERS - Ľubor Tománek; Denisa Zambová (University of Banja Luka, Faculty of physical education and sport, 2012)
Shooting practice in youth basketball is "cornerstone" for proper shooting technique, likely, enabling the player to get high shooting percentage in a Professional League (adults). The purpose of this study was to verify the efficiency of the shooting fundamental program (n = 18, age 9.85 ± .53). Experimental groups were used in these results. The results showed the effect of shooting fundamental program. Shooting test the lay-ups after this period of an experiment was increased by +1.83 successful attempts in comparison with the result in the control time (+1.45) (p < .01). These findings show that efficiency of basketball shooting fundamental program increase shooting percentage during the period of an experiment.